2014
DOI: 10.2478/s11686-014-0214-6
|View full text |Cite
|
Sign up to set email alerts
|

Infections with cardiopulmonary and intestinal helminths and sarcoptic mange in red foxes from two different localities in Denmark

Abstract: Monitoring parasitic infections in the red fox is essential for obtaining baseline knowledge on the spread of diseases of veterinary and medical importance. In this study, screening for cardiopulmonary and intestinal helminths and sarcoptic mange (Sarcoptes scabiei) was done on 118 foxes originating from two distinct localities in Denmark, (Copenhagen) greater area and southern Jutland. Fifteen parasite species were recorded in 116 foxes (98.3%), nine parasitic species are of zoonotic potential. Parasite diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 74 publications
7
41
7
Order By: Relevance
“…Differently from Soldati et al (1976), Magi et al (2009Magi et al ( , 2016 and Capelli et al (2003), we couldn't find any Toxascaris leonina. This actually agrees with most studies on helminths of foxes, in which a higher prevalence of T. canis was usually reported (LoosFrank & Zeyhle 1982;Richards et al 1995;Vervaeke et al 2005;Al-Sabi et al 2014). Only one wolf was infected with T. canis and at an extremely low intensity (i.e.…”
Section: : 3% Of 109 Foxes)supporting
confidence: 80%
See 3 more Smart Citations
“…Differently from Soldati et al (1976), Magi et al (2009Magi et al ( , 2016 and Capelli et al (2003), we couldn't find any Toxascaris leonina. This actually agrees with most studies on helminths of foxes, in which a higher prevalence of T. canis was usually reported (LoosFrank & Zeyhle 1982;Richards et al 1995;Vervaeke et al 2005;Al-Sabi et al 2014). Only one wolf was infected with T. canis and at an extremely low intensity (i.e.…”
Section: : 3% Of 109 Foxes)supporting
confidence: 80%
“…Dipylidium caninum (Linnaeus, 1758), a fleatransmitted tapeworm, has often shown low levels of prevalence in European countries (Loos-Frank & Zeyhle 1982;Richards et al 1995;Vervaeke et al 2005;Al-Sabi et al 2014). In our research we found a prevalence of 3.5% (Table I), which is consistent with previous studies in Emilia-Romagna (Guberti & Poglayen 1991: 2.6% of 153 foxes; Capelli et al…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of helminth infections in red foxes from Denmark has been well studied, showing prevalences of A. vasorum of 48.6 % (n = 1040) in Northern Zealand, an endemic area within Denmark (Saeed et al 2006). A recent study showed that A. vasorum is abundant in foxes (n = 70) from the Copenhagen area with a prevalence of 80 %, but not in foxes (n = 48) from Southern Jutland (Al-Sabi et al 2014). A lot of research is also done in the UK, which harbours some highly endemic foci and where A. vasorum has spread beyond traditional endemic areas (Blehaut et al 2014;Kirk et al 2014).…”
Section: Discussionmentioning
confidence: 99%